KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DAN PENCATATAN SIPIL KECAMATAN PINGGIR KABUPATEN BENGKALIS - Nurhayati "; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The phenomenon of the administration of public services carried out by the government is still faced with services that are not yet effective and efficient and the quality of human resources is not adequate. Referring to the Bengkalis Regent Regulation No. 19 of 2009 concerning the position, main tasks, function details of tasks, making standard operating procedures (SOP) which applies to all sub-districts in Bengkalis district. There are many on social media about complaints from residents of the suburbs and the results of observations about the poor service of the UPT service for population and civil registration in the suburbs of Bengkalis Regency. This study aims to determine and analyze the quality of services in the UPT of the population and civil registration office in the suburbs of Bengkalis Regency. This study uses a descriptive qualitative method with 18 research informants who are residents as well as employees of the UPT population and civil registration service at the outskirts of Bengkalis Regency. Based on the results of this study, the quality of service at the population and civil registration services in the suburbs of the Bengkalis Regency Keywords: service quality, public service and population administration.